Gastroprotective and Antioxidant Effects of Montelukast on Indomethacin-Induced Gastric Ulcer in Rats - Gunnur Ozbakis Dengiz; Fehmi Odabasoglu; Zekai Halici; Elif Cadirci; Halis Suleyman (Elsevier, 2007)
Montelukast, a selective reversible cysteinyl leukotriene D4-receptor (LTD4 receptor) antagonist, is used in the treatment of asthma. We have investigated alterations in the glutathione (GSH) and activity levels of antioxidative enzymes [superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), and glutathione reductase (GR)] and myeloperoxidase (MPO), as markers of the ulceration process following oral administration of montelukast, lansoprazole, famotidine, and ranitidine, respectively, in rats with indomethacin-induced ulcers. In the present study, we found that 1) montelukast, lansoprazole, famotidine, and ranitidine all reduced the development of indomethacin-induced gastric damage, with this reduction occurring at a greater magnitude for montelukast, famotidine, and lansoprazole than for ranitidine; 2) montelukast and ranitidine both alleviated increases in the activity levels of CAT and GST enzymes resulting from gastric injury; 3) montelukast and ranitidine both ameliorated depressions in the GSH and activity levels of SOD and GR enzymes caused by indomethacin administration; and 4) all doses of montelukast, lansoprazole, and ranitidine decreased amplification of MPO activity resulting from induced gastric injuries. These results suggest that the gastroprotective effects of montelukast on indomethacin-induced ulcerations can be attributed to its ameliorating effect on oxidative damage and MPO activity. Keywords:: montelukast, indomethacin, gastroprotective effect, myeloperoxidase, antioxidant enzyme